PENEGAKAN HUKUM DI INDONESIA UNTUK SI KAYA DAN SI MISKIN - Sufiyah, Putri Cahya (Dinamika Hukum & Masyarakat, 2020)
ABSTRACT The state of Indonesia is a state of law. People will definitely be punished if they are caught violating the applicable laws in the country. However, law enforcement is often considered unfair to some people. In Indonesia, the people tend to be divided into several social classes. Even though everyone has been guaranteed the right to get equal treatment before the law, the facts on the ground show that violators of the rule of law will definitely get punishment according to their social class. This is what makes the emergence of a term that "the law will be blunt up and pointed down". This study aims to find out more about legal cases committed by the rich (upper class people) and the poor (lower class people). The method used in this research is qualitative. The results of this study indicate that there is legal discrimination in similar legal cases committed by the rich (upper class people) and the poor (lower class people). Keywords: Law Enforcement, Rich, Poor